HUBUNGAN DAYA LEDAK OTOT TUNGKAI DENGAN KEMAMPUAN SHOOTING EKSTRAKURIKULER SEPAKBOLA SMA NEGERI 1 KAMPAR - Tri Wahyu Agusti; Slamet '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on the researcher’s observation of football exstracurricular in 1 kampar high school. Researcher found many student have frequent errors in shooting, when the student shooting ball not on target so in the game often lose, shooting technique a weakness of student in football extracurricular of SMAN 1 Kampar. The purpose of this research is to see how much the correlation of explosive power leg muscle with ability shooting ball of football extracurricular in SMAN 1 Kampar. Population in this research were all students in football extracurricular in SMAN 1 Kampar amount 22 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 22 people. Research instrument used explosive power leg muscles data test and the result of shooting ball. Data were analyzed by product moment correlation.Based on research results, it can be concluded as follows : Shows that there is corelations explosive power leg muscles with ability shooting, which shows rhitung>rtabelpadaα=0,05Key word : Power, Leg Muscles, Shooting, Football.